Redress at a higher education institution: Art processes and image theatre as embodied and rhizomatic learning - Costandius, Elmarie; Brand, Amelda; de Villiers, Gera (Critical Studies in Teaching and Learning, 2023)
In January 2019, a visual redress project was launched at Stellenbosch University, South Africa that introduced new artworks and contextualised existing statues around campus. However, it became clear that this dual installation and contextualisation did not sufficiently provide a means to address structural, systemic racial injustices inherent in the colonial and apartheid past; a more embodied way of engagement was needed. Therefore, workshops combining art and performance were introduced where lecturers, students and community members worked through social, political, and personal issues. This entanglement of art, performance, bodies, and space became a method that changed and evolved with each workshop. It was a dynamic, fluid, and relational process that could not be prescriptive as it depended on the elements constituting it. In this article, the various workshops are discussed, and it is shown how new topics and affective reactions at each workshop emerged through the art processes and practices.